State capture, grand corruption, petty corruption dan hubungannya dengan investasi di Indonesia (Komisi Pemberantasan Korupsi, 2023)
This study aims to find the correlations between various types of corruption, namely state cap-ture, grand corruption, and petty corruption, with foreign direct investment and domestic investment in Indonesia. Using ordinary least squares method, this study analyzes data on corruption court decisions that occurred in 509 regencies from 2015 to 2019. The results reveal that, whilst domestic investment shows clear and significant correlation only with grand corruption, the foreign direct investment has definite and significant correlations with both grand and petty corruption. In addition, grand corruption has a stronger correlation with investment, especially with the foreign direct investment, in comparison to petty corrup-tion. The state capture corruption, on the other hand, shows no significant correlation to either foreign direct investment or domestic investment. These results highlight that the high level of investment in Indonesia is accompanied by an increase in the number of corruptions, especially large-scale corruption such as grand corruption.